Effect of Age on Semen Quality and Freezability in Sahiwal Bulls - Gautam, Anshul; Singh, Pawan; Sriranga, K. R.; Arya, Shruti (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted at ICAR-National Dairy Research Institute, Karnal, Haryana, India during Feb–May 2023 to find out the age window at which the bull produces quality semen. Fifteen Sahiwal bulls were selected and classified into three age groups (n=5 in each group) -(2–3.5), (>3.5–8) and (>8–12) years. Semen was collected twice a week with two ejaculates on each collection. Fresh and extended frozen semen was analysed at fortnightly interval. The data was subjected to statistical analysis by one-way Analysis of Variance (ANOVA) using SPSS software version 26.0 to draw scientific inferences. The results revealed that the mean value of semen volume (ml), sperm concentration (106 ml-1), mass motility was high (p<0.05) in the >8-12 age group. Individual motility was high (p<0.05) in the >3.5–8 age group. Mean value of viability (%), HOST (%), Acrosome integrity (%) was lower in 2-3.5 age group for fresh as well as frozen semen. Post thaw motility was high (p<0.05) in >3.5-8 age group. In incubation test, the post thaw motility of the >3.5–8 age group was high (p<0.05) at 0, 90 and 120 min. Therefore, it can be concluded from the study that semen quality of Sahiwal bulls is influenced by age and it is better to use Sahiwal bulls only after 3.5 years of age and best semen quality is obtained from bulls of >3.5-8 years of age.